Pengaruh Harga, Kualitas Pelayanan, dan Lokasi terhadap Minat Beli Konsumen pada Rumah Makan Mie Endess Arosbaya - Uswatun Hasanah; Octaviana Arisinta; Yusrianto Sholeh (Universitas Batanghari, 2022)
Indonesia has a culinary diversity that stretches from west to east Indonesia and is still embedded in the social life of the local community. Each region has its own unique food because each culture is different from one another. For example, Madurese cuisine is synonymous with spicy salty taste. The development of the Food House business in Bangkalan is progressing very quickly. One example in Bangkalan is Mie whip, Mie endes, and so on. Many things are taken into consideration by consumers to arrive at a decision to choose a particular restaurant or company. The restaurant management must try to meet the criteria that are considered by consumers, both in terms of service quality, price and location so that they can easily attract consumer buying interest. One of them at the Endess Mie Restaurant is a noodle restaurant that is currently popular among young people. Based on the background that arises above, it makes researchers interested in conducting research on